Microstructural evolution and mechanics of hot-drawn CNT-reinforced polymeric nanofibers. (November 2016) - Cai, Jizhe; Chawla, Sneha; Naraghi, Mohammad
Abstract: To unravel reinforcing effect of CNTs in polymeric nanofibers, polyacrylonitrile (PAN)/SWNTs nanofibers with various CNTs content (0.1–0.5 wt%) were electrospun. Nanofibers were hot-drawn to enhance PAN chains and SWNT alignment. The microstructure of composite nanofibers was studied via polarized Raman and IR spectroscopy, x-ray diffraction, and TEM imaging. The study pointed to a marked contribution of SWNTs at low SWNT contents (0.1 wt%) to chain mobility and alignment during electrospinning. Evidence of volume changes was reported during hot-drawing, depending on CNT content, alluding to arrangement of CNTs in nanofibers. Indirect evidence of SWNT agglomeration, adversely affecting reinforcement efficiency at higher SWNT contents, was presented. Hot-drawing above T g of PAN led to massive chain and SWNT alignment and orientation-induced crystallization. The most promising mechanical performance was achieved in hot-drawn ribbons with low SWNT content, where formation of an interphase –evidenced in TEM images – led to significant enhancement of effective reinforcement modulus of ∼2.15 ± 1.97 TPa, with the average value considerably higher than modulus of CNTs. This study demonstrates a clear path to prepare PAN nanofibers with high chain alignment as precursor for the next generation of carbon nanofibers with unprecedented strength and modulus.